Betongpålars miljöpåverkan - Valett,Martin; Johansson,Jacob (2014)
The need to perform basic construction reinforcements is growing all the time because in our larger cities they have already built in most places. The untouched land where there is no settlement is due to poor geological conditions. This makes piling more common today, and in the future the usage will grow even more. Concrete is now and has long been one of Sweden's most common construction materials. The material has outstanding traits with a good durability that has made the material valuable in comparison with many others. This report aims to examine and compare the impact of two different types of concrete piles. The reason for this is that environmental issues are becoming increasingly more important in society and the realization that the earth's limited resources clearly shows that humans must take responsibility and act to take care of the environment. The construction sector is today one of the major environmental pressures in society. Today's standard piles consist of cement, reinforcement additives and aggregates of various sizes. The most common concrete pile has a dimension of 275x275 mm. The new fiber pole with dimension 235x235 mm has a halved amount of reinforcement and where steel fiber is added to provide a greater load carrying capacity. This new fiber pole can directly replace a 275x275 mm pole as it has the same load capacity. This leads to a direct reduction of concrete resulting in less material usage and reduced transportations, which means a reduced CO2 emission. The size of the decrease is due to a number of different parameters. The main factors for the decline of the carbon footprint is reduced material consumption due to the fiber pile is of a smaller cross section. The smaller cross section also leads to lower transport emissions upon delivery to the customer when trucks can carry more of the smaller piles. This case study is based on carbon dioxide equivalents to investigate any impact on the climate for the production of concrete. The results show that if one replaces all standard piles for fiber concrete piles for a year in Sweden, The gain is roughly 2600 tons of carbon dioxide that are reduced and is not released into the atmosphere. The results of the report are a direct figure of piles climate impact in terms of greenhouse gas emissions. It should be mentioned that there are other environmental benefits such as reduced emissions of acid gases and a reduced use of gravel.
Keywords: betong; pålning; grundläggning; miljö; koldioxidekvivalenter